Re-appraising self and other in the English translation of contemporary Chinese political discourse. (October 2018) - Li, Tao; Xu, Fang
Abstract: Drawing on appraisal system (Martin and White, 2005), this paper examines the variation of attitudes towards China and other countries by analyzing a corpus of the Chinese-English translation of evaluative epithets in graduation—the sub-category of appraisal system—in contemporary Chinese political discourse from 2000 to 2017. The findings suggest that: (1) translation shifts do exist in the translation of graduation epithets, particularly in the form of zero translation, though the cardinal principle of remaining faithful to the original Chinese political discourse is respected; (2) statistical analysis indicates a significant difference in the variation of attitudes towards China and other countries through translation shifts, and the variations of attitudes are in such a way that attitude towards China becomes less positive while attitude towards other countries less negative in the translation of political discourse from Chinese into English. It is argued that the translation participants' adherence to the General Strategy of Politeness (Leech, 2014) can partially account for the research findings. It should also be noted that the basis for their adherence, ideologically speaking, is to serve the Self's interests.